2005
DOI: 10.1590/s0036-46652005000100006
|View full text |Cite
|
Sign up to set email alerts
|

Environmental straits of Cryptococcus neoformans variety grubii in the city of Santos, SP, Brazil

Abstract: This study involved a total of 116 samples, 79 taken from pigeon droppings and 37 of atmospheric air taken close to accumulations of excrement. Cryptococcus neoformans var. grubii was isolated from 11 (13.9%) of these samples. Other species of Cryptococcus were also isolated from these samples, such as C. albidus (12.6%) and C. laurentii (8.9%). C. neoformans was not isolated from the air samples, though C. albidus (5.4%) was. All the strains of C. neoformans were found to belong to the A serotype (C. neoforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
9

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 28 publications
3
21
1
9
Order By: Relevance
“…grubii isolates to fluconazole, itraconazole and 5-flucytosine compared with that of the clinical isolates is in contrast to the findings of some investigators who found that antifungal susceptibility was not related to the clinical or environmental origin of strains (Franzot & Hamdan, 1996;Moraes et al, 2003;Trilles et al, 2004). Of relevance here is the report by Soares et al (2005) stating that a solitary isolate of C. neoformans var. grubii from pigeon excreta was resistant to fluconazole (MIC 64 mg ml 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…grubii isolates to fluconazole, itraconazole and 5-flucytosine compared with that of the clinical isolates is in contrast to the findings of some investigators who found that antifungal susceptibility was not related to the clinical or environmental origin of strains (Franzot & Hamdan, 1996;Moraes et al, 2003;Trilles et al, 2004). Of relevance here is the report by Soares et al (2005) stating that a solitary isolate of C. neoformans var. grubii from pigeon excreta was resistant to fluconazole (MIC 64 mg ml 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of C. neoformans from avian excreta has been reported by several authors 3,7,16,19,20 . REZENDE (2002) evaluated the presence of C. neoformans in pigeon and canary droppings in the urban area of the city of Alfenas and found the yeast in 11.11% of the samples analyzed.…”
Section: Discussionmentioning
confidence: 91%
“…Cryptococcus neoformans em relação a diferentes antifúngicos tem sido estudada por diversos autores 2,6,8,9 . Entretanto, há poucos dados comparativos de valores de CIM entre isolados clínicos e ambientais.…”
Section: A Sensibilidade In Vitro Deunclassified